Knowledge, attitude and practice of pregnant women on gender preference, prenatal sex determination and female feticide - Kapoor, Gitanjali; Kumar, Dinesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Sex ratio is defined as the number of females per thousand males. The objectives were to study the knowledge, attitude and the practice of pregnant women on gender preference, prenatal sex determination and female feticide. Methods: It was a hospital based cross-sectional study. The present study was undertaken among the 204 newly registered pregnant women attending the hospital in Marh block of Jammu district, Jammu and Kashmir, India. A pre-designed, pre-tested and structured questionnaire was used in the study. The data collection technique was a personnel interview of the study subjects. Results: The mean age of study subjects was 25.39±3.6 years. A majority (75.5%) of the pregnant women did not show any gender preference, followed by male preference (13.73%) and female preference (10.78%). Only 70.59% and 67.65%, of the total subjects were aware that prenatal sex determination and female feticide are illegal, respectively. Awareness regarding prenatal sex determination and female feticide increased with the level of education. Conclusions: There is a need to educate pregnant women about the impact of negative sex ratio on the society and about the penalization for violation of the PCPNDT act.